FIRST MEGATHERIINES (XENARTHRA, PHYLLOPHAGA, MEGATHERIIDAE) FROM THE URUMACO (LATE MIOCENE) AND CODORE (PLIOCENE) FORMATIONS, ESTADO FALCON, VENEZUELA - Carlini A.A.; Brandoni D.; Sanchez R. (My University, 2006)
Two new genera and species of Megatheriinae are described from the Neogene of Venezuela: Urumaquia robusta gen. et sp. nov. from the Urumaco Formation (Late Miocene) and Proeremotherium eljebe gen. et sp. nov. from the Codore Formation (Pliocene). These represent only the second Tertiary record of the subfamily at low latitudes in South America. The anatomical features of Urumaquia robusta suggest that the levels of the Urumaco Formation bearing the fauna here studied may not be correlated with the Laventan SALMA, but with Chasicoan-Huayquerian SALMAs.
Keywords: NEW TAXA; MIO-PLIOCENE; GROUND SLOTHS; VENEZUELA; SOUTH AMERICA; Pliocene; Miocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен